PERLINDUNGAN HUKUM ANAK TERLANTAR: : Kajian Prespektif Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak - Rudy Catur Rohman Kusmayadi; Musleh (Jurnal Penelitian Ilmiah INTAJ, 2022)
Abandoned children are children who do not get the same rights as children. their families and relatives are not able to carry out their obligations so that the needs of children's rights are not met. As stated in Law no. 35 of 2014 concerning child protection, which reads; "Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop, and participate optimally in accordance with human dignity, and receive protection from violence and discrimination". It is a major problem regarding the protection of neglected children in Indonesia. Regarding the future, whether with Law Number 35 of 2014 is a solution to the problem of the number of neglected children in Indonesia whose future is still not guaranteed. The research used is a qualitative research method, with an approach using normative/doctrinal law which in foreign legal literature is commonly referred to as legal research and without the addition of other meanings, namely the opinion of some legal scholars can be said to be pure legal research. The government and local government have the authority to protect neglected children as regulated in Law Number 35 of 2014 including: 1) regarding housing guarantees, 2) guarantees for maintenance and care, 3) children's rights to obtain identity from the state. Children in terms of national and state life are the future of the nation and the next generation of the ideals of the nation, so that the state is obliged to fulfill the rights of every child to survival, growth and development, participation, protection from acts of violence and discrimination.